2009
DOI: 10.1109/ispsd.2009.5157996
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of stationary destructive cathode-side filaments in p<inf>+</inf>-n<inf>&#x2212;</inf>-n<sup>+</sup> diodes

Abstract: Analyzing the dynamics of current filaments is essential for a correct understanding of SOA limitations. Current filaments can occur during the reverse-recovery period of p + -n − -n + diodes. In this work, we apply the results from an analysis of the plasma-front dynamics for the one-dimensional case to conditions under which current filaments appear in the depletion layers due to dynamic avalanche. We show that the anode-side plasma front velocity is higher in the vicinity of the filament than far away from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…4b). It is therefore supposed that spikes can contribute to the destruction mechanism suggested in [2]. In [2], unrealistic hard-switching conditions were necessary to create a destructive filament in simulation.…”
Section: T [Us] X Filamentmentioning
confidence: 99%
See 2 more Smart Citations
“…4b). It is therefore supposed that spikes can contribute to the destruction mechanism suggested in [2]. In [2], unrealistic hard-switching conditions were necessary to create a destructive filament in simulation.…”
Section: T [Us] X Filamentmentioning
confidence: 99%
“…It is therefore supposed that spikes can contribute to the destruction mechanism suggested in [2]. In [2], unrealistic hard-switching conditions were necessary to create a destructive filament in simulation. If once a filament has driven a spike by thermomigration from the cathode side into the base region of the diode, the diode can be destroyed during the next pulse.…”
Section: T [Us] X Filamentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the appearances of the filaments at the anode and cathode sides do not necessarily lead to the diode destruction, however, the eventual filament by a transition from avalanche-induced into thermally driven filament could cause the local temperature rise inside the device, this is an important factor of the device failure [3][4][5]. In order to improve the fast and soft recovery characteristic of high voltage diode, some technologies by improved structures and carrier lifetime controls were implemented.…”
Section: Introductionmentioning
confidence: 99%
“…As the lattice temperature raises, the carrier mobility, the electic field and the intrinsic carrier concentration will all be influenced. And as a result, it can be lead to the device failure, either in stationary or dynamic situation [3,4].…”
Section: Introductionmentioning
confidence: 99%